2017
DOI: 10.1038/srep42689
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dairy by-product waste milk on the microbiomes of different gastrointestinal tract components in pre-weaned dairy calves

Abstract: The community structure of colonised bacteria in the gastrointestinal tracts (GITs) of pre-weaned calves is affected by extrinsic factors, such as the genetics and diet of the calves; however, the dietary impact is not fully understood and warrants further research. Our study revealed that a total of 6, 5, 2 and 10 bacterial genera showed biologically significant differences in the GITs of pre-weaned calves fed four waste-milk diets: acidified waste milk, pasteurised waste milk, untreated bulk milk, and untrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0
8

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 55 publications
(59 reference statements)
4
38
0
8
Order By: Relevance
“…Deng et al [28] showed that an acidified waste milk diet produced similar bacterial diversity in colon mucosa and digesta samples and rectum feces in calves, with present results at the generic level. The abundance of Bacteroidetes in the feces of calves fed AM before weaning positively correlated with the colonization resistance of gut harmful microorganisms, which would prevent the entry of pathogens in the early stage of infection [25,29].…”
Section: Microbial Diversity In the Feces Of Calves Fed Am And Pmsupporting
confidence: 72%
“…Deng et al [28] showed that an acidified waste milk diet produced similar bacterial diversity in colon mucosa and digesta samples and rectum feces in calves, with present results at the generic level. The abundance of Bacteroidetes in the feces of calves fed AM before weaning positively correlated with the colonization resistance of gut harmful microorganisms, which would prevent the entry of pathogens in the early stage of infection [25,29].…”
Section: Microbial Diversity In the Feces Of Calves Fed Am And Pmsupporting
confidence: 72%
“…Fibrobacter belongs to the poorly defined Fibrobacteres phylum, which is characterized by high cellulolytic activity and capable of degrading complex plant fiber ( Qi et al, 2005 ). It was reported that increased abundance of Fibrobacter resulted in high concentration of SCFAs in rumen of dairy cows ( Deng et al, 2017 ). Meanwhile, the population of Fibrobacter was increased in finishing pigs fed a diet containing 10% CB in our previous study ( Liu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, unclassified Ruminococcaceae and Lachnospiraceae, Bacteroides, Alistipes, Akkermansia, Clostridium, Ruminococcus , and Prevotella have been found to predominate in the feces (Callaway et al, 2010 ; Deng et al, 2017 ; Li et al, 2017 ). Unclassified Ruminococcaceae and Lachnospiraceae, Prevotella , and Ruminococcus have also been detected in 742 rumen samples of 32 types of ruminants from all over the world and might be considered as the “core bacterial microbiome” at the genus level (Henderson et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%